EVALUATION AND ANALYSIS OF THE SUSTAINABLE WASTE-TO-ENERGY SYSTEM PERFORMANCE FOR THE POULTRY FARM - Xuejun QIAN; Yulai YANG; Raghulkumar CHANDRASEKARAN; Seong LEE (Journal of Construction Project Management and Innovation)
Poultry litter is one type of biomass and waste generated from the poultry farms. However, excess land application of poultry litter caused eutrophication problems of surface waters coming from the watershed and destroyed the aquatic ecology. Co-combustion of poultry litter and coal were widely studied in fluidized bed combustor as an alternative disposal method during last two decades. However, there are severe environmental problems (i.e., gaseous emissions) and public health impact associated with the poultry litter and coal co-combustion process. In this study, poultry litter and natural gas co-combustion was investigated in the lab-scale waste-to-energy system to provide a sustainable and cost-effective disposal route for poultry farms. This waste-to-energy system integrates the Stirling Engine (SE), Shell-Tube Heat Exchanger (STHE) and the lab-scale Swirling Fluidized Bed Combustor (SFBC) with other systems (e.g., cyclone, air supply system, fuel feeding system). Measures of heat transfer effect, electricity output and gas emissions levels were used to evaluate the lab-scale waste-to-energy system performance. Results indicated that lab-scale waste-to-energy system can produce electricity (close to 1 kW) and hot water (57.2°C) while reducing NOx and SO2 emissions during the poultry litter and natural gas co-combustion process. In addition, energy flow analysis indicated that SE and STHE system might use 14.7% and 21.0% of total energy input in fuels, respectively, to generate useful energy.  In addition, a sustainable life cycle of poultry litter was built and suggested to process poultry wastes in the poultry farms.